Digital Archive Management Through the Srikandi Application at the Education Office of Gresik District - Alawiyah, Lutviatul (Jurnal Pengabdian Nusantara, 2025)
This study aims to provide strategic recommendations in improving the quality of digital archive management, so that it can support better public services and meet the demands of the digitalization era. The SRIKANDI application was created as an effort to support digital transformation in archive management, improve work efficiency, and comply with national archival regulations. This study is a qualitative study with a descriptive approach with data collection techniques through interviews, observations, and document studies. The data analysis techniques used are data collection, data reduction, data presentation, and data verification. This study analyzes the implementation of the SRIKANDI application and its impact on digital archive management, as well as obstacles in its use. The results of the study show that the SRIKANDI application plays a significant role in accelerating the archive management process, reducing the use of physical documents, and increasing transparency. However, the implementation of this application faces various challenges, such as limited technological infrastructure, lack of user understanding, and the need for further training. This study also reveals that compliance with archival standards has begun to form, although it still requires further optimization.